Effect of Increased Temperature on Native and Alien Nuisance Cyanobacteria from Temperate Lakes: An Experimental Approach - Ksenija Savadova; Hanna Mazur-Marzec; Jūratė Karosienė; Jūratė Kasperovičienė; Irma Vitonytė; Anna Toruńska-Sitarz; Judita Koreivienė (Toxins, 2018)
In response to global warming, an increase in cyanobacterial blooms is expected. In this work, the response of two native species of Planktothrix agardhii and Aphanizomenon gracile, as well as the response of two species alien to Europe—Chrysosporum bergii and Sphaerospermopsis aphanizomenoides—to gradual temperature increase was tested. The northernmost point of alien species distribution in the European continent was recorded. The tested strains of native species were favoured at 20⁻28 °C. Alien species acted differently along temperature gradient and their growth rate was higher than native species. Temperature range of optimal growth rate for S. aphanizomenoides was similar to native species, while C. bergii was favoured at 26⁻30 °C but sensitive at 18⁻20 °C. Under all tested temperatures, non-toxic strains of the native cyanobacteria species prevailed over the toxic ones. In P. agardhii, the decrease in concentration of microcystins and other oligopeptides with the increasing temperature was related to higher growth rate. However, changes in saxitoxin concentration in A. gracile under different temperatures were not detected. Accommodating climate change perspectives, the current work showed a high necessity of further studies of temperature effect on distribution and toxicity of both native and alien cyanobacterial species.